Improving the economics of building energy code change: A review of the inputs and assumptions of economic models. (May 2016) - Berry, Stephen; Davidson, Kathryn
Abstract: Building energy code change in Australia, and many other developed nations, is subject to standardised economic tests, with a net present value calculation at the heart of the economic analysis. Although many nations have introduced minimum energy efficiency standards for residential and commercial buildings, increases in stringency have been hindered by limitations to the range of private and societal impacts typically incorporated in regulatory impact assessments. Given the policy move towards net zero energy homes, a more comprehensive set of inputs and robust assumptions are needed to support further regulatory change. Yet the literature provides substantial evidence of many private and societal costs and benefits not commonly incorporated into the economic assessments that underpin regulatory change. Drawing on a case study of Australian and UK residential regulatory change assessments, this paper highlights limitations to the range of inputs and assumptions currently incorporated within the economic arguments applied during residential energy code change processes, and presents a more comprehensive economic argument that could support further stringency improvements.